Development of Magnetic Abrasive Finishing Process to Finish Brass Rods - Singh, Iqbal; Kaushal, Gagandeep; Sidhu, Hazor Singh (Asian Review of Mechanical Engineering, 2014)
Surface finish plays an important role in manufacturing industry. There are many traditional processes used to reduce the surface roughness, Magnetic abrasive is one of them. In present study a setup was prepared for machining of brass rods. The setup was designed to study the effect of various parameters such as working gap, machining time and grit size. Abrasive particles (Emery) and magnetic particles (Iron) were used. Taguchi approach was used to reduce the number of experiments. L9 orthogonal array was used. “Talysurf” surface roughness tester was used for measurement of roughness. Results showed that most optimum working gap is 8mm, grit size 180 grit and 12 minutes machining time. MINITAB software was used for further analysis.